2018
DOI: 10.1098/rstb.2017.0267
|View full text |Cite
|
Sign up to set email alerts
|

Sources of children's knowledge about death and dying

Abstract: In the last century, decreases in infant and child mortality, urbanization and increases in healthcare efficacy have reduced children's personal exposure to death and dying. So how do children acquire accurate conceptions of death in this context? In this paper, we discuss three sources of children's learning about death and dying, namely, direct experience of death, parental communication about death and portrayals of death in the media and the arts. We conclude with recommendations about how best to teach mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
1
24
0
4
Order By: Relevance
“…However, the question remains as to whether they are aware of what it means when a partner remains permanently inert, and whether we can gain any insight into this question. Research studies in developmental psychology have shown that the understanding of death in human children can be defined and measured through several dimensions (Speece & Brent 1984;Kenyon 2001;Slaughter 2005;Longbottom & Slaughter 2018). From 4 to 10 years of age, children successively master four main dimensions related to the concept of mortality: (1) Irreversibility: a dead individual cannot return to life, (2) Universality: all living beings must eventually die, (3) Cessation: all bodily and mental functions cease upon death, (4) Causation: the breakdown of bodily functions is due to external and internal causes.…”
Section: Awareness Of Mortalitymentioning
confidence: 99%
“…However, the question remains as to whether they are aware of what it means when a partner remains permanently inert, and whether we can gain any insight into this question. Research studies in developmental psychology have shown that the understanding of death in human children can be defined and measured through several dimensions (Speece & Brent 1984;Kenyon 2001;Slaughter 2005;Longbottom & Slaughter 2018). From 4 to 10 years of age, children successively master four main dimensions related to the concept of mortality: (1) Irreversibility: a dead individual cannot return to life, (2) Universality: all living beings must eventually die, (3) Cessation: all bodily and mental functions cease upon death, (4) Causation: the breakdown of bodily functions is due to external and internal causes.…”
Section: Awareness Of Mortalitymentioning
confidence: 99%
“…Talking about death and dying with young children has been reported as one of the more challenging conversations for parents even when compared with conversations regarding other topics such as reproduction, ageing, and diagnosis of a serious illness [ 58 ]. Studies have shown that caregivers who are more anxious about an impending death were also more likely to avoid these crucial conversations and had a higher likelihood to utilize euphemisms when discussing death.…”
Section: Anticipatory Griefmentioning
confidence: 99%
“…Вопрос о мотивирующем потенциале медийных текстов является трудным, нерешенным и требующим внимания в силу возрастающего значения медийных сообщений [28,29,30,31]. Суждение о психологической деструкции или созидательности медианарративов должно опираться на комплексный психологический анализ, учитывающий не только содержательный уровень медиатекста, но и уровень организации его формы.…”
Section: результатыunclassified